Computer Application to Gain Competitiveness Advantages In E-Commerce - L Ismawati; A Setiawan (Peneliti.net, 2020)
The development of the era of globalization is a challenge for Small and Medium Enterprises (SMEs) to continue to survive. Information technology, especially social media, offers benefits for SMEs to improve their marketing. One of the developing SMEs is Distribution Store (Distro), an SME engaged in trading with a business focus on selling clothing as well as accessories of its own production. This research conducted to determine the use of social media and its benefits to SMEs in the Bandung area. This study was an observational study of SMEs and social media used. The subjects selected by purposive sampling. The results showed that the most widely used social media were websites, Facebook and Instagram. Social media used by SMEs to make personal contact with consumers, promote, record what is needed by consumers and deliver responses to consumers. Social media is an effective communication medium for SMEs that can increase the scope of market share and help business decisions. The use of social media can increase sales by more than 100% if done consistently and update information every day. The conclusion of this study is social media has the potential to increase market share and sales volume, therefore it needs to be used optimally and consistently.